To flee, or not to flee? Using innate defensive behaviours to investigate rapid perceptual decision-making through subcortical circuits in mouse models of autism - Burnett, Laura
The process of detecting and evaluating sensory information to guide behaviour is termed perceptual decision-making (PDM), and is critical for the ability of an organism to interact with its external world. Individuals with autism, a neurodevelopmental condition primarily characterised by social and communication difficulties, frequently exhibit altered sensory processing and PDM difficulties are widely reported. Recent technological advancements have pushed forward our understanding of the genetic changes accompanying this condition, however our understanding of how these mutations affect the function of specific neuronal circuits and bring about the corresponding behavioural changes remains limited. Here, we use an innate PDM task, the looming avoidance response (LAR) paradigm, to identify a convergent behavioural abnormality across three molecularly distinct genetic mouse models of autism (Cul3, Setd5 and Ptchd1). Although mutant mice can rapidly detect threatening visual stimuli, their responses are consistently delayed, requiring longer to initiate an appropriate response than their wild-type siblings. Mutant animals show abnormal adaptation in both their stimulus- evoked escape responses and exploratory dynamics following repeated stimulus presentations. Similarly delayed behavioural responses are observed in wild-type animals when faced with more ambiguous threats, suggesting the mutant phenotype could arise from a dysfunction in the flexible control of this PDM process. Our knowledge of the core neuronal circuitry mediating the LAR facilitated a detailed dissection of the neuronal mechanisms underlying the behavioural impairment. In vivo extracellular recording revealed that visual responses were unaffected within a key brain region for the rapid processing of visual threats, the superior colliculus (SC), indicating that the behavioural delay was unlikely to originate from sensory impairments. Delayed behavioural responses were recapitulated in the Setd5 model following optogenetic stimulation of the excitatory output neurons of the SC, which are known to mediate escape initiation through the activation of cells in the underlying dorsal periaqueductal grey (dPAG). In vitro patch-clamp recordings of dPAG cells uncovered a stark hypoexcitability phenotype in two out of the three genetic models investigated (Setd5 and Ptchd1), that in Setd5, is mediated by the misregulation of voltage-gated potassium channels. Overall, our results show that the ability to use visual information to drive efficient escape responses is impaired in three diverse genetic mouse models of autism and that, in one of the models studied, this behavioural delay likely originates from differences in the intrinsic excitability of a key subcortical node, the dPAG. Furthermore, this work showcases the use of an innate behavioural paradigm to mechanistically dissect PDM processes in autism.

Neural control of optic flow-based navigation in Drosophila melanogaster - Pokusaeva, Victoria
During navigation, animals can infer the structure of the environment by computing the optic flow cues elicited by their own movements, and subsequently use this information to instruct proper locomotor actions. These computations require a panoramic assessment of the visual environment in order to disambiguate similar sensory experiences that may require distinct behavioral responses. The estimation of the global motion patterns is therefore essential for successful navigation. Yet, our understanding of the algorithms and implementations that enable coherent panoramic visual perception remains scarce. Here I pursue this problem by dissecting the functional aspects of interneuronal communication in the lobula plate tangential cell network in Drosophila melanogaster. The results presented in the thesis demonstrate that the basis for effective interpretation of the optic flow in this circuit are stereotyped synaptic connections that mediate the formation of distinct subnetworks, each extracting a particular pattern of global motion. Firstly, I show that gap junctions are essential for a correct interpretation of binocular motion cues by horizontal motion-sensitive cells. HS cells form electrical synapses with contralateral H2 neurons that are involved in detecting yaw rotation and translation. I developed an FlpStop-mediated mutant of a gap junction protein ShakB that disrupts these electrical synapses. While the loss of electrical synapses does not affect the tuning of the direction selectivity in HS neurons, it severely alters their sensitivity to horizontal motion in the contralateral side. These physiological changes result in an inappropriate integration of binocular motion cues in walking animals. While wild-type flies form a binocular perception of visual motion by non-linear integration of monocular optic flow cues, the mutant flies sum the monocular inputs linearly. These results indicate that rather than averaging signals in neighboring neurons, gap-junctions operate in conjunction with chemical synapses to mediate complex non-linear optic flow computations. Secondly, I show that stochastic manipulation of neuronal activity in the lobula plate tangential cell network is a powerful approach to study the neuronal implementation of optic flow-based navigation in flies. Tangential neurons form multiple subnetworks, each mediating course-stabilizing response to a particular global pattern of visual motion. Application of genetic mosaic techniques can provide sparse optogenetic activation of HS cells in numerous combinations. These distinct combinations of activated neurons drive an array of distinct behavioral responses, providing important insights into how visuomotor transformation is performed in the lobula plate tangential cell network. This approach can be complemented by stochastic silencing of tangential neurons, enabling direct assessment of the functional role of individual tangential neurons in the processing of specific visual motion patterns. Taken together, the findings presented in this thesis suggest that establishing specific activity patterns of tangential cells via stereotyped synaptic connectivity is a key to efficient optic flow-based navigation in Drosophila melanogaster.

Environmental dynamics shape perceptual decision bias - Charlton, Julie A.; Mlynarski, Wiktor F; Bai, Yoon H.; Hermundstad, Ann M.; Goris, Robbe L.T. (PLoS Computational Biology)
To interpret the sensory environment, the brain combines ambiguous sensory measurements with knowledge that reflects context-specific prior experience. But environmental contexts can change abruptly and unpredictably, resulting in uncertainty about the current context. Here we address two questions: how should context-specific prior knowledge optimally guide the interpretation of sensory stimuli in changing environments, and do human decision-making strategies resemble this optimum? We probe these questions with a task in which subjects report the orientation of ambiguous visual stimuli that were drawn from three dynamically switching distributions, representing different environmental contexts. We derive predictions for an ideal Bayesian observer that leverages knowledge about the statistical structure of the task to maximize decision accuracy, including knowledge about the dynamics of the environment. We show that its decisions are biased by the dynamically changing task context. The magnitude of this decision bias depends on the observer’s continually evolving belief about the current context. The model therefore not only predicts that decision bias will grow as the context is indicated more reliably, but also as the stability of the environment increases, and as the number of trials since the last context switch grows. Analysis of human choice data validates all three predictions, suggesting that the brain leverages knowledge of the statistical structure of environmental change when interpreting ambiguous sensory signals.

Panoramic visual statistics shape retina-wide organization of receptive fields - Gupta, Divyansh; Mlynarski, Wiktor F; Sumser, Anton L; Symonova, Olga; Svaton, Jan; Jösch, Maximilian A (Nature Neuroscience)
Statistics of natural scenes are not uniform - their structure varies dramatically from ground to sky. It remains unknown whether these non-uniformities are reflected in the large-scale organization of the early visual system and what benefits such adaptations would confer. Here, by relying on the efficient coding hypothesis, we predict that changes in the structure of receptive fields across visual space increase the efficiency of sensory coding. We show experimentally that, in agreement with our predictions, receptive fields of retinal ganglion cells change their shape along the dorsoventral retinal axis, with a marked surround asymmetry at the visual horizon. Our work demonstrates that, according to principles of efficient coding, the panoramic structure of natural scenes is exploited by the retina across space and cell-types.

Panoramic functional gradients across the mouse retina - Kirillova, Kseniia
All visual experiences of the vertebrates begin with light being converted into electrical signals by the eye retina. Retinal ganglion cells (RGCs) are the neurons of the innermost layer of the mammal retina, and they transmit visual information to the rest of the brain. It has been shown that RGCs vary in their morphology and genetic profiles, moreover they can be unambiguously grouped into subtypes that share the same morphological and/or molecular properties. However, in terms of RGCs function, it remains unclear how many distinct types there are and what response properties their typology relies on. Even given the recent studies that successfully classified RGCs in a patch of the retina [1] and in scotopic conditions [2], the question remains whether the found subtypes persist across the entire retina. In this work, using a novel imaging method, we show that, when sampled from a large portion of the retina, RGCs can not be clearly divided into functional subtypes. We found that in photopic conditions, which implies more prominent natural scene statistic differences across the visual field, response properties can be exhibited by cells differently depending on their location in the retina, which leads to formation of a gradient of features rather than distinct classes. This finding suggests that RGCs follow a global organization across the visual field of the animal, adapting each RGC subtype to the requirements imposed by the natural scene statistics.

Strand asymmetry influences mismatch resolution during single-strand annealing - Pokusaeva, Victoria; Diez, Aránzazu Rosado; Espinar, Lorena; Pérez, Albert Torelló; Filion, Guillaume J. (Genome Biology)
Background: Biases of DNA repair can shape the nucleotide landscape of genomes at evolutionary timescales. The molecular mechanisms of those biases are still poorly understood because it is difficult to isolate the contributions of DNA repair from those of DNA damage. Results: Here, we develop a genome-wide assay whereby the same DNA lesion is repaired in different genomic contexts. We insert thousands of barcoded transposons carrying a reporter of DNA mismatch repair in the genome of mouse embryonic stem cells. Upon inducing a double-strand break between tandem repeats, a mismatch is generated if the break is repaired through single-strand annealing. The resolution of the mismatch showed a 60–80% bias in favor of the strand with the longest 3′ flap. The location of the lesion in the genome and the type of mismatch had little influence on the bias. Instead, we observe a complete reversal of the bias when the longest 3′ flap is moved to the opposite strand by changing the position of the double-strand break in the reporter. Conclusions: These results suggest that the processing of the double-strand break has a major influence on the repair of mismatches during single-strand annealing.

Fast, high-throughput production of improved rabies viral vectors for specific, efficient and versatile transsynaptic retrograde labeling - Sumser, Anton L; Jösch, Maximilian A; Jonas, Peter M; Ben Simon, Yoav (eLife)
To understand the function of neuronal circuits, it is crucial to disentangle the connectivity patterns within the network. However, most tools currently used to explore connectivity have low throughput, low selectivity, or limited accessibility. Here, we report the development of an improved packaging system for the production of the highly neurotropic RVdGenvA-CVS-N2c rabies viral vectors, yielding titers orders of magnitude higher with no background contamination, at a fraction of the production time, while preserving the efficiency of transsynaptic labeling. Along with the production pipeline, we developed suites of ‘starter’ AAV and bicistronic RVdG-CVS-N2c vectors, enabling retrograde labeling from a wide range of neuronal populations, tailored for diverse experimental requirements. We demonstrate the power and flexibility of the new system by uncovering hidden local and distal inhibitory connections in the mouse hippocampal formation and by imaging the functional properties of a cortical microcircuit across weeks. Our novel production pipeline provides a convenient approach to generate new rabies vectors, while our toolkit flexibly and efficiently expands the current capacity to label, manipulate and image the neuronal activity of interconnected neuronal circuits in vitro and in vivo.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Change in the neurochemical signature and morphological development of the parvocellular isthmic projection to the avian tectum - Reyes‐Pinto, Rosana; Ferrán, José L.; Vega Zuniga, Tomas A; González‐Cabrera, Cristian; Luksch, Harald; Mpodozis, Jorge; Puelles, Luis; Marín, Gonzalo J. (Journal of Comparative Neurology)
Neurons can change their classical neurotransmitters during ontogeny, sometimes going through stages of dual release. Here, we explored the development of the neurotransmitter identity of neurons of the avian nucleus isthmi parvocellularis (Ipc), whose axon terminals are retinotopically arranged in the optic tectum (TeO) and exert a focal gating effect upon the ascending transmission of retinal inputs. Although cholinergic and glutamatergic markers are both found in Ipc neurons and terminals of adult pigeons and chicks, the mRNA expression of the vesicular acetylcholine transporter, VAChT, is weak or absent. To explore how the Ipc neurotransmitter identity is established during ontogeny, we analyzed the expression of mRNAs coding for cholinergic (ChAT, VAChT, and CHT) and glutamatergic (VGluT2 and VGluT3) markers in chick embryos at different developmental stages. We found that between E12 and E18, Ipc neurons expressed all cholinergic mRNAs and also VGluT2 mRNA; however, from E16 through posthatch stages, VAChT mRNA expression was specifically diminished. Our ex vivo deposits of tracer crystals and intracellular filling experiments revealed that Ipc axons exhibit a mature paintbrush morphology late in development, experiencing marked morphological transformations during the period of presumptive dual vesicular transmitter release. Additionally, although ChAT protein immunoassays increasingly label the growing Ipc axon, this labeling was consistently restricted to sparse portions of the terminal branches. Combined, these results suggest that the synthesis of glutamate and acetylcholine, and their vesicular release, is complexly linked to the developmental processes of branching, growing and remodeling of these unique axons.

Evolutionary and structural constraints influencing apolipoprotein A‐I amyloid behavior - Gisonno, Romina A.; Masson, Tomas; Ramella, Nahuel A.; Barrera, Exequiel E.; Romanowski, Víctor; Tricerri, M. Alejandra (Proteins: Structure, Function, and Bioinformatics)
Apolipoprotein A‐I (apoA‐I) has a key function in the reverse cholesterol transport. However, aggregation of apoA‐I single point mutants can lead to hereditary amyloid pathology. Although several studies have tackled the biophysical and structural consequences introduced by these mutations, there is little information addressing the relationship between the evolutionary and structural features that contribute to the amyloid behavior of apoA‐I. We combined evolutionary studies, in silico mutagenesis and molecular dynamics (MD) simulations to provide a comprehensive analysis of the conservation and pathogenic role of the aggregation‐prone regions (APRs) present in apoA‐I. Sequence analysis demonstrated that among the four amyloidogenic regions described for human apoA‐I, only two (APR1 and APR4) are evolutionary conserved across different species of Sarcopterygii. Moreover, stability analysis carried out with the FoldX engine showed that APR1 contributes to the marginal stability of apoA‐I. Structural properties of full‐length apoA‐I models suggest that aggregation is avoided by placing APRs into highly packed and rigid portions of its native fold. Compared to silent variants extracted from the gnomAD database, the thermodynamic and pathogenic impact of amyloid mutations showed evidence of a higher destabilizing effect. MD simulations of the amyloid variant G26R evidenced the partial unfolding of the alpha‐helix bundle with the concomitant exposure of APR1 to the solvent, suggesting an insight into the early steps involved in its aggregation. Our findings highlight APR1 as a relevant component for apoA‐I structural integrity and emphasize a destabilizing effect of amyloid variants that leads to the exposure of this region.
Keywords: Molecular Biology; Biochemistry; Structural Biology

Ventro-dorsal hippocampal pathway gates novelty-induced contextual memory formation - Fredes Tolorza, Felipe A; Silva Sifuentes, Maria A; Koppensteiner, Peter; Kobayashi, Kenta; Jösch, Maximilian A; Shigemoto, Ryuichi (Current Biology)
Novelty facilitates formation of memories. The detection of novelty and storage of contextual memories are both mediated by the hippocampus, yet the mechanisms that link these two functions remain to be defined. Dentate granule cells (GCs) of the dorsal hippocampus fire upon novelty exposure forming engrams of contextual memory. However, their key excitatory inputs from the entorhinal cortex are not responsive to novelty and are insufficient to make dorsal GCs fire reliably. Here we uncover a powerful glutamatergic pathway to dorsal GCs from ventral hippocampal mossy cells (MCs) that relays novelty, and is necessary and sufficient for driving dorsal GCs activation. Furthermore, manipulation of ventral MCs activity bidirectionally regulates novelty-induced contextual memory acquisition. Our results show that ventral MCs activity controls memory formation through an intra-hippocampal interaction mechanism gated by novelty.

A specialized reciprocal connectivity suggests a link between the mechanisms by which the superior colliculus and parabigeminal nucleus produce defensive behaviors in rodents - Deichler, Alfonso; Carrasco, Denisse; Lopez-Jury, Luciana; Vega Zuniga, Tomas A; Marquez, Natalia; Mpodozis, Jorge; Marin, Gonzalo (Scientific Reports)
The parabigeminal nucleus (PBG) is the mammalian homologue to the isthmic complex of other vertebrates. Optogenetic stimulation of the PBG induces freezing and escape in mice, a result thought to be caused by a PBG projection to the central nucleus of the amygdala. However, the isthmic complex, including the PBG, has been classically considered satellite nuclei of the Superior Colliculus (SC), which upon stimulation of its medial part also triggers fear and avoidance reactions. As the PBG-SC connectivity is not well characterized, we investigated whether the topology of the PBG projection to the SC could be related to the behavioral consequences of PBG stimulation. To that end, we performed immunohistochemistry, in situ hybridization and neural tracer injections in the SC and PBG in a diurnal rodent, the Octodon degus. We found that all PBG neurons expressed both glutamatergic and cholinergic markers and were distributed in clearly defined anterior (aPBG) and posterior (pPBG) subdivisions. The pPBG is connected reciprocally and topographically to the ipsilateral SC, whereas the aPBG receives afferent axons from the ipsilateral SC and projected exclusively to the contralateral SC. This contralateral projection forms a dense field of terminals that is restricted to the medial SC, in correspondence with the SC representation of the aerial binocular field which, we also found, in O. degus prompted escape reactions upon looming stimulation. Therefore, this specialized topography allows binocular interactions in the SC region controlling responses to aerial predators, suggesting a link between the mechanisms by which the SC and PBG produce defensive behaviors.

Anatomical specializations related to foraging in the visual system of a nocturnal insectivorous bird, the band-winged nightjar (Aves: Caprimulgiformes) - Salazar, Juan Esteban; Severin, Daniel; Vega Zuniga, Tomas A; Fernández-Aburto, Pedro; Deichler, Alfonso; Sallaberry A., Michel; Mpodozis, Jorge (Brain, Behavior and Evolution)
Nocturnal animals that rely on their visual system for foraging, mating, and navigation usually exhibit specific traits associated with living in scotopic conditions. Most nocturnal birds have several visual specializations, such as enlarged eyes and an increased orbital convergence. However, the actual role of binocular vision in nocturnal foraging is still debated. Nightjars (Aves: Caprimulgidae) are predators that actively pursue and capture flying insects in crepuscular and nocturnal environments, mainly using a conspicuous “sit-and-wait” tactic on which pursuit begins with an insect flying over the bird that sits on the ground. In this study, we describe the visual system of the band-winged nightjar (Systellura longirostris), with emphasis on anatomical features previously described as relevant for nocturnal birds. Orbit convergence, determined by 3D scanning of the skull, was 73.28°. The visual field, determined by ophthalmoscopic reflex, exhibits an area of maximum binocular overlap of 42°, and it is dorsally oriented. The eyes showed a nocturnal-like normalized corneal aperture/axial length index. Retinal ganglion cells (RGCs) were relatively scant, and distributed in an unusual oblique-band pattern, with higher concentrations in the ventrotemporal quadrant. Together, these results indicate that the band-winged nightjar exhibits a retinal specialization associated with the binocular area of their dorsal visual field, a relevant area for pursuit triggering and prey attacks. The RGC distribution observed is unusual among birds, but similar to that of some visually dependent insectivorous bats, suggesting that those features might be convergent in relation to feeding strategies.

A micro-CT-based method for quantitative brain lesion characterization and electrode localization - Masís, Javier; Mankus, David; Wolff, Steffen; Guitchounts, Grigori; Jösch, Maximilian A; Cox, David (Scientific Reports)
Lesion verification and quantification is traditionally done via histological examination of sectioned brains, a time-consuming process that relies heavily on manual estimation. Such methods are particularly problematic in posterior cortical regions (e.g. visual cortex), where sectioning leads to significant damage and distortion of tissue. Even more challenging is the post hoc localization of micro-electrodes, which relies on the same techniques, suffers from similar drawbacks and requires even higher precision. Here, we propose a new, simple method for quantitative lesion characterization and electrode localization that is less labor-intensive and yields more detailed results than conventional methods. We leverage staining techniques standard in electron microscopy with the use of commodity micro-CT imaging. We stain whole rat and zebra finch brains in osmium tetroxide, embed these in resin and scan entire brains in a micro-CT machine. The scans result in 3D reconstructions of the brains with section thickness dependent on sample size (12–15 and 5–6 microns for rat and zebra finch respectively) that can be segmented manually or automatically. Because the method captures the entire intact brain volume, comparisons within and across studies are more tractable, and the extent of lesions and electrodes may be studied with higher accuracy than with current methods.

Flexible learning-free segmentation and reconstruction of neural volumes - Shabazi, Ali; Kinnison, Jeffery; Vescovi, Rafael; Du, Ming; Hill, Robert; Jösch, Maximilian A; Takeno, Marc; Zeng, Hongkui; Da Costa, Nuno; Grutzendler, Jaime; Kasthuri, Narayanan; Scheirer, Walter (Scientific Reports)
Imaging is a dominant strategy for data collection in neuroscience, yielding stacks of images that often scale to gigabytes of data for a single experiment. Machine learning algorithms from computer vision can serve as a pair of virtual eyes that tirelessly processes these images, automatically detecting and identifying microstructures. Unlike learning methods, our Flexible Learning-free Reconstruction of Imaged Neural volumes (FLoRIN) pipeline exploits structure-specific contextual clues and requires no training. This approach generalizes across different modalities, including serially-sectioned scanning electron microscopy (sSEM) of genetically labeled and contrast enhanced processes, spectral confocal reflectance (SCoRe) microscopy, and high-energy synchrotron X-ray microtomography (μCT) of large tissue volumes. We deploy the FLoRIN pipeline on newly published and novel mouse datasets, demonstrating the high biological fidelity of the pipeline’s reconstructions. FLoRIN reconstructions are of sufficient quality for preliminary biological study, for example examining the distribution and morphology of cells or extracting single axons from functional data. Compared to existing supervised learning methods, FLoRIN is one to two orders of magnitude faster and produces high-quality reconstructions that are tolerant to noise and artifacts, as is shown qualitatively and quantitatively.

“Shepherd’s crook” neurons drive and synchronize the enhancing and suppressive mechanisms of the midbrain stimulus selection network - Garrido-Charad, Florencia; Vega Zuniga, Tomas A; Gutiérrez-Ibáñez, Cristián; Fernandez, Pedro; López-Jury, Luciana; González-Cabrera, Cristian; Karten, Harvey J.; Luksch, Harald; Marín, Gonzalo J. (Proceedings of the National Academy of Sciences)
The optic tectum (TeO), or superior colliculus, is a multisensory midbrain center that organizes spatially orienting responses to relevant stimuli. To define the stimulus with the highest priority at each moment, a network of reciprocal connections between the TeO and the isthmi promotes competition between concurrent tectal inputs. In the avian midbrain, the neurons mediating enhancement and suppression of tectal inputs are located in separate isthmic nuclei, facilitating the analysis of the neural processes that mediate competition. A specific subset of radial neurons in the intermediate tectal layers relay retinal inputs to the isthmi, but at present it is unclear whether separate neurons innervate individual nuclei or a single neural type sends a common input to several of them. In this study, we used in vitro neural tracing and cell-filling experiments in chickens to show that single neurons innervate, via axon collaterals, the three nuclei that comprise the isthmotectal network. This demonstrates that the input signals representing the strength of the incoming stimuli are simultaneously relayed to the mechanisms promoting both enhancement and suppression of the input signals. By performing in vivo recordings in anesthetized chicks, we also show that this common input generates synchrony between both antagonistic mechanisms, demonstrating that activity enhancement and suppression are closely coordinated. From a computational point of view, these results suggest that these tectal neurons constitute integrative nodes that combine inputs from different sources to drive in parallel several concurrent neural processes, each performing complementary functions within the network through different firing patterns and connectivity.

A micro-CT-based method for characterising lesions and locating electrodes in small animal brains - Masís, Javier; Mankus, David; Wolff, Steffen; Guitchounts, Grigori; Jösch, Maximilian A; Cox, David (Journal of visualized experiments)
Lesion and electrode location verification are traditionally done via histological examination of stained brain slices, a time-consuming procedure that requires manual estimation. Here, we describe a simple, straightforward method for quantifying lesions and locating electrodes in the brain that is less laborious and yields more detailed results. Whole brains are stained with osmium tetroxide, embedded in resin, and imaged with a micro-CT scanner. The scans result in 3D digital volumes of the brains with resolutions and virtual section thicknesses dependent on the sample size (12-15 and 5-6 µm per voxel for rat and zebra finch brains, respectively). Surface and deep lesions can be characterized, and single tetrodes, tetrode arrays, electrolytic lesions, and silicon probes can also be localized. Free and proprietary software allows experimenters to examine the sample volume from any plane and segment the volume manually or automatically. Because this method generates whole brain volume, lesions and electrodes can be quantified to a much higher degree than in current methods, which will help standardize comparisons within and across studies.

The genetic encoded toolbox for electron microscopy and connectomics - Shigemoto, Ryuichi; Jösch, Maximilian A (WIREs Developmental Biology)
Developments in bioengineering and molecular biology have introduced a palette of genetically encoded probes for identification of specific cell populations in electron microscopy. These probes can be targeted to distinct cellular compartments, rendering them electron dense through a subsequent chemical reaction. These electron densities strongly increase the local contrast in samples prepared for electron microscopy, allowing three major advances in ultrastructural mapping of circuits: genetic identification of circuit components, targeted imaging of regions of interest and automated analysis of the tagged circuits. Together, the gains from these advances can decrease the time required for the analysis of targeted circuit motifs by over two orders of magnitude. These genetic encoded tags for electron microscopy promise to simplify the analysis of circuit motifs and become a central tool for structure‐function studies of synaptic connections in the brain. We review the current state‐of‐the‐art with an emphasis on connectomics, the quantitative analysis of neuronal structures and motifs.

Mosaic analysis with double markers reveals distinct sequential functions of Lgl1 in neural stem cells - Beattie, Robert J; Postiglione, Maria P; Burnett, Laura; Laukoter, Susanne; Streicher, Carmen; Pauler, Florian; Xiao, Guanxi; Klezovitch, Olga; Vasioukhin, Valeri; Ghashghaei, Troy; Hippenmeyer, Simon (Neuron)
The concerted production of neurons and glia by neural stem cells (NSCs) is essential for neural circuit assembly. In the developing cerebral cortex, radial glia progenitors (RGPs) generate nearly all neocortical neurons and certain glia lineages. RGP proliferation behavior shows a high degree of non-stochasticity, thus a deterministic characteristic of neuron and glia production. However, the cellular and molecular mechanisms controlling RGP behavior and proliferation dynamics in neurogenesis and glia generation remain unknown. By using mosaic analysis with double markers (MADM)-based genetic paradigms enabling the sparse and global knockout with unprecedented single-cell resolution, we identified Lgl1 as a critical regulatory component. We uncover Lgl1-dependent tissue-wide community effects required for embryonic cortical neurogenesis and novel cell-autonomous Lgl1 functions controlling RGP-mediated glia genesis and postnatal NSC behavior. These results suggest that NSC-mediated neuron and glia production is tightly regulated through the concerted interplay of sequential Lgl1-dependent global and cell intrinsic mechanisms.

DynamicRoots: A software platform for the reconstruction and analysis of growing plant roots - Symonova, Olga; Topp, Christopher; Edelsbrunner, Herbert (PLoS One)
We present a software platform for reconstructing and analyzing the growth of a plant root system from a time-series of 3D voxelized shapes. It aligns the shapes with each other, constructs a geometric graph representation together with the function that records the time of growth, and organizes the branches into a hierarchy that reflects the order of creation. The software includes the automatic computation of structural and dynamic traits for each root in the system enabling the quantification of growth on fine-scale. These are important advances in plant phenotyping with applications to the study of genetic and environmental influences on growth.

3D phenotyping and quantitative trait locus mapping identify core regions of the rice genome controlling root architecture - Topp, Christopher; Iyer Pascuzzi, Anjali; Anderson, Jill; Lee, Cheng; Zurek, Paul; Symonova, Olga; Zheng, Ying; Bucksch, Alexander; Mileyko, Yuriy; Galkovskyi, Taras; Moore, Brad; Harer, John; et al. (PNAS)
Identification of genes that control root system architecture in crop plants requires innovations that enable high-throughput and accurate measurements of root system architecture through time. We demonstrate the ability of a semiautomated 3D in vivo imaging and digital phenotyping pipeline to interrogate the quantitative genetic basis of root system growth in a rice biparental mapping population, Bala x Azucena. We phenotyped >1,400 3D root models and >57,000 2D images for a suite of 25 traits that quantified the distribution, shape, extent of exploration, and the intrinsic size of root networks at days 12, 14, and 16 of growth in a gellan gum medium. From these data we identified 89 quantitative trait loci, some of which correspond to those found previously in soil-grown plants, and provide evidence for genetic tradeoffs in root growth allocations, such as between the extent and thoroughness of exploration. We also developed a multivariate method for generating and mapping central root architecture phenotypes and used it to identify five major quantitative trait loci (r2 = 24-37%), two of which were not identified by our univariate analysis. Our imaging and analytical platform provides a means to identify genes with high potential for improving root traits and agronomic qualities of crops.

The adaptive topology of a digital image - Edelsbrunner, Herbert; Symonova, Olga
In order to enjoy a digital version of the Jordan Curve Theorem, it is common to use the closed topology for the foreground and the open topology for the background of a 2-dimensional binary image. In this paper, we introduce a single topology that enjoys this theorem for all thresholds decomposing a real-valued image into foreground and background. This topology is easy to construct and it generalizes to n-dimensional images.